Early Neurological Improvement Predicts Clinical Outcome After Thrombectomy for Distal Medium Vessel Occlusions - Wang, Maud; Farouki, Yousra; Hulscher, Franny; Mine, Benjamin; Bonnet, Thomas; Elens, Stephanie; Vazquez Suarez, Juan; Jodaitis, Lise; Ligot, Noémie; Naeije, Gilles; Lubicz, Boris; Guenego, Adrien (Frontiers in Neurology, 2022)
Background and Purpose: Good clinical outcome predictors have been established in mechanical thrombectomy (MT) for acute ischemic stroke (AIS) caused by large vessel occlusion (LVO). An early neurological improvement (ENI), defined as a reduction of ≥8 on the National-Institutes of Health Stroke-Scale (NIHSS) compared with the baseline score, or an NIHSS of 0 or 1 at 24 hours after MT, is a strong predictor of favorable outcome. We aimed to study the impact of ENI after MT for distal, medium vessel occlusions (DMVO). Methods: We retrospectively analyzed the data of consecutive patients who underwent MT for a primary DMVO in one large academic center. We compared clinical outcomes between DMVO patients stratified by ENI. Multivariate analyses were performed to determine the impact of ENI on good 90-day outcome (modified Rankin scale of 0-2) and identify factors contributing to ENI. Results: Between January 2018 and January 2021, 61 patients underwent a MT for an AIS with a primary DMVO. An ENI was seen in 24 (39%) patients (ENI+). Outcomes were significantly better in ENI+ patients, with 83% achieving a good outcome at 3 months versus 43% for ENI- patients (p=0.019). ENI was an independent predictive factor of good clinical outcome even after adjusting for potential confounding factors (Odds-ratio 12.49 [1.49-105.01], p=0.020). Use of IVtPA (Odds-ratio 6.59 [1.82-23.89], p=0.004) was a positive predictor of ENI. Conclusion: ENI at day 1 following MT for DMVO stroke is a strong independent predictor of good to excellent 3-months clinical outcome.